Distribution changes of plankton communities in the harbour Porto Montenegro (South Adriatic Sea) - Pestorić, Branka (2018)
Plankton data (phyto, zoo and ichthyo) that were collected monthly from March 2016 to February 2017 in the harbour ?Porto Montenegro? and the referent station (Tivat Bay) were analysed to determine if there are any differences in plankton distribution, composition and diversity among sites. In contrast to phytoplankton and zooplankton, whose diversity and spatial distribution are driven considerably by temperature and salinity (phytoplankton) and inter-species interaction, affinity for aggregation with specific water masses (zooplankton), the spatial dynamics of ichthyoplankton is significantly dependent on the aggregation of adult populations, rates of mortality, and physical processes that affect the position and retention of organisms. Anchovy early life stages and the dominance of this species in referent station during all months of investigation, especially in August, caused significant difference among sites. We found that unfavourable conditions for adult fish aggregation in the harbour area ?Porto Montenegro? could be the reason for driving the differences in the ichthyoplankton spatial distribution compared with Bay area, while phytoplankton and zooplankton data didn?t show significant differences among sites.